2013
DOI: 10.1088/0031-9155/58/18/6525
|View full text |Cite
|
Sign up to set email alerts
|

Toward a web-based real-time radiation treatment planning system in a cloud computing environment

Abstract: To exploit the potential dosimetric advantages of intensity modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT), an in-depth approach is required to provide efficient computing methods. This needs to incorporate clinically related organ specific constraints, Monte Carlo (MC) dose calculations, and large-scale plan optimization. This paper describes our first steps toward a web-based real-time radiation treatment planning system in a cloud computing environment (CCE). The Amazon Elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Similarly, Miras et al [ 62 ] used Microsoft Azure with up to 64 virtual machines of different sizes to measure a speedup of up to 37x. A more complex calculation is performed by Na et al [ 63 ] who uses Amazon cloud with up to 100 worker instances for a speedup of 10-14x. The difference in the speedup is caused by the ability to parallelize the algorithms and the overhead for worker management and data communication.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, Miras et al [ 62 ] used Microsoft Azure with up to 64 virtual machines of different sizes to measure a speedup of up to 37x. A more complex calculation is performed by Na et al [ 63 ] who uses Amazon cloud with up to 100 worker instances for a speedup of 10-14x. The difference in the speedup is caused by the ability to parallelize the algorithms and the overhead for worker management and data communication.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature research revealed 22 theoretical papers that did not describe a specific cloud project but provided more common information on cloud computing in healthcare [ 4 - 6 , 8 , 14 , 23 , 24 , 26 , 49 - 52 , 56 , 79 - 87 ]. 12 articles include descriptions of basic conceptual work for cloud projects, but included no creation of a real system [ 16 , 30 , 35 , 46 , 53 , 54 , 63 , 77 , 88 - 92 ]. If applications are described they are usually in a prototype status [ 1 , 7 , 10 - 13 , 15 , 17 - 22 , 28 , 29 , 31 , 33 , 34 , 39 - 45 , 47 , 48 , 55 , 58 , 59 , 61 - 70 , 72 - 75 , 93 - 101 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations